Prevalence of Hearing Aids Usage and Their Outcomes in Old Age Population: Hearing Aids Usage and their Outcomes - Khan , Muhammad Bilal Raza; Badar, Syeda Asfara; Saleem, Khadija; Khalid, Faiqa; Arslan, Muhammad; Abdullah, Muhammad; Ashraf, Naeem; Aslam, Eruj Fatima; Akhtar , Daniel (Pakistan Journal of Health Sciences, 2023)
Hearing loss caused by old age or presbycusis is the type that occurs gradually as people age. Many people cover up their handicap by wearing hearing aids. Some sounds are amplified by hearing aids so that people with hearing loss can listen, converse, and engage in more everyday activities. Objective: To determine the prevalence of hearing aids usage and the outcomes of hearing aids in old age population. Methods: Cross Sectional observational study was conducted to find the prevalence of usage and outcomes of hearing aids in old age population on a sample of 161 patients with both male and female with non-probability purposive sampling technique. The research was carried out in one hospital (University of Lahore Teaching Hospital). Duration of this study was 6 months from Jan 2023 to June 2023. Patients 50 years of age and older were included. Patients with other comorbid factors like congenital anomalies, conductive hearing loss were excluded. The data were gathered using a self-structured questionnaire. Data were analyzed through (SPSS) version 27.0 package. Results: Out of 161 patients, 86 (53.4%) of the participants were men, and 75 (46.6%) were women. Only 57 of them (35.4%) used hearing aids; 52 (91.2%) individuals got benefit from hearing aids in daily activities; and 51 (89.5%) individuals were confident that using hearing aids would compensate their disability. Conclusions: This study found that among hearing aid users, the majority of participants got benefit from their hearing aids.